Structural Significance of the Mid-level Décollement Within the Western Sichuan Fold-And-Thrust Belt (WSFTB), Insights From Sandbox Modeling - Sun, Chuang; Li, Zhigang; Wu, Shimin; He, Zhiyuan; Zhao, Shaotian; Wang, Panfei (Frontiers in Earth Science, 2021)
The WSFTB is located outboard of the eastern Tibetan Plateau, western China. It has received great attention due to high earthquake risks and rich resources of oil and gas. For both issues, the detailed structural configuration and deformation mechanism behind it are of great importance, but remain unclear due to the complexity created by the presence of multiple décollements. The effect of regionally-distributed shallow Triassic salt décollement (SD) and the basal one (BD) has been well understood. In this paper, we focus on the third décollement situated between them. We conducted three sandbox experiments by varying this mid-level décollement (MD) from absence to presence, and from frictional to viscous, to test the effect on diversity of regional structural configuration. Our experimental results illustrated that 1) Absence of MD facilitated decoupling on SD, forming the greatest contrast between subsurface deformation front and the blind one beneath SD; 2) Frictional MD itself showed little decoupling, while its weakness reduced the bulk strength of deep structural level, lowering decoupling effect on SD and leading to approximating deformation fronts in the shallow and deep; 3) The viscous MD, along with SD relieved the resistance on their interbed layer. Consequently, the fastest deformation propagation rate and farthest deformation front (in all the experiments) occurred in the middle structural level. The modeled fold and thrust structures are comparable with the southern, central and northern WSFTB respectively, suggesting that varied MD may control the along-strike structural variations presented. The results also indicate that MD can alter the deformation partition in depth of any other multiple décollement system.